2021
DOI: 10.1055/a-1366-9379
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Syndrome with Monoclonal Gammopathy—A Mechanism for Recurrent Thrombosis?

Abstract: Not Applicable

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In addition, a history, complete physical examination, and biochemical tests, such as serum paraprotein and light chain assay, should be performed to exclude solid organ or haematological malignancies. Our recent study showed that some APS patients with recurrent thrombosis despite adequate anticoagulation had a paraprotein [49]. Doyle et al showed that the percentage of other autoimmune disorders among these nine patients was low and there was a predilection for arterial thrombosis [49].…”
Section: Recurrent Thrombosis While On Treatmentmentioning
confidence: 76%
“…In addition, a history, complete physical examination, and biochemical tests, such as serum paraprotein and light chain assay, should be performed to exclude solid organ or haematological malignancies. Our recent study showed that some APS patients with recurrent thrombosis despite adequate anticoagulation had a paraprotein [49]. Doyle et al showed that the percentage of other autoimmune disorders among these nine patients was low and there was a predilection for arterial thrombosis [49].…”
Section: Recurrent Thrombosis While On Treatmentmentioning
confidence: 76%
“…No patients had a diagnosis of malignancy. Patients 1 and 3 were tested for monoclonal gammopathy 16 and JAK2 V617F, 17 neither of which were present. Patient 2 has not been tested for these.…”
Section: Resultsmentioning
confidence: 99%
“…Because APS and monoclonal gamma globulin disease increase the risk of thrombosis, thrombotic events may be caused by the combined effect of these conditions ( 52 ). Recently, Doyle et al ( 53 ) described a new discovery of a small number of patients with thrombotic APS and monoclonal gamma globulin receiving anticoagulation therapy having a higher incidence of recurrent thrombosis than patients without accessory protein. When thrombotic APS develops, long-term anticoagulation is required.…”
Section: Discussionmentioning
confidence: 99%